The question of satire and the figuration of humanitism in Memorias póstumas de Brás Cubas - dos Reis Corrêa, Ana Laura (Inter Litteras, 2019)
This text tries to answer, first of all, to questions proposed by the recurrent mode of composition of the narrative adopted by Machado de Assis more visibly after the publication of Memorias póstumas de Brás Cubas, in 1880. According to our hypothesis, this mode of composition achieves a powerful realistic effect upon being founded on the creative method of satire. The presence of satire in the work of Machado de Assis has already been studied by various critics of his, who understood it as a formal affiliation to the menipean satire and Lukács’ tradition, but not as a lever to erect the realism of his works. We find in the text of G. Lukács “The question of satire” a problematization that we found consistent and adequate to examine the place of satire in the composition of posthumous memories, especially in what it says about the immediate contrast between essence and phenomenon required by satirical figuration. As it is not possible in this article to cover in detail the totality of Machado’s novel, we chose chapter CXVII, “humanitismo”, as an object of analysis, because, because of its deep articulation with the narrative as a whole, you can tell us a lot about the presence of satire as a creative method that guarantees the realistic scope of the work as a whole.